E Efektivitas Pengendalian Pengeluaran Kas PPLN Disperindag Jawa Timur - Niken Purwadhani Putri; Ardiansyah (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2024)
In carrying out the duties and functions of governance in the government bureaucracy, one element that is an important component is matters in the financial sector. Cash disbursements are one of the elements contained in financial affairs, where cash disbursements must be carried out with great care, guided by applicable regulations, and must be managed and accounted for properly. This research was conducted with the aim of finding out cash disbursement procedures in the Foreign Trade Development Sector (PPLN Sector), which is one of the work units in the East Java Province Industry and Trade Service and how controls are implemented over cash disbursement procedures. This research was conducted using observation study methods, interviews and literature studies. The data analysis method used in this research is a qualitative descriptive method, namely interpreting and describing data related to events that occurred with respondents. It is hoped that the results of this research can be a reference for related parties to review cash disbursement procedures periodically so that cash disbursement procedures are always better and create effective, efficient and transparent financial administration.